The legend of Sleepy Hollow - Zornow, Jeff (Graphic horror, 2008)
A graphic novel adaptation of "The Legend of Sleepy Hollow," the story of Ichabod Crane, an irritating schoolteacher who falls prey to his own superstitious belief in a terrifying headless horseman.